2013
DOI: 10.1055/s-0033-1351019
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of St. Johnʼs Wort (Hypericum perforatum)

Abstract: St. John's wort (Hypericum perforatum) has been intensively investigated for its antidepressive activity, but dermatological applications also have a long tradition. Topical St. John's wort preparations such as oils or tinctures are used for the treatment of minor wounds and burns, sunburns, abrasions, bruises, contusions, ulcers, myalgia, and many others. Pharmacological research supports the use in these fields. Of the constituents, naphthodianthrones (e.g., hypericin) and phloroglucinols (e.g., hyperforin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 71 publications
4
104
0
9
Order By: Relevance
“…These effects would be in keeping with those seen in several investigations in animal models that reported that hyperforin regulated inflammation associated with immune-based diseases such as irritable bowel syndrome, Parkinson's disease and Alzheimer's diseases (Kraus et al 2007;Mohanasundari & Sabesan 2007;Mozaffari et al 2011). Similarly, the current results would be in line with earlier studies that reported on how H. perforatum could be used as an anti-inflammatory, an anti-oxidant and/or a wound healing agent (Süntar et al 2010;Wolfle et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These effects would be in keeping with those seen in several investigations in animal models that reported that hyperforin regulated inflammation associated with immune-based diseases such as irritable bowel syndrome, Parkinson's disease and Alzheimer's diseases (Kraus et al 2007;Mohanasundari & Sabesan 2007;Mozaffari et al 2011). Similarly, the current results would be in line with earlier studies that reported on how H. perforatum could be used as an anti-inflammatory, an anti-oxidant and/or a wound healing agent (Süntar et al 2010;Wolfle et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…It has been used in traditional medicine for treatment of mild-to-moderate depression (Barnes et al 2001). HP has also been used as an anti-oxidant, anti-inflammatory and wound-healing herbal drug (Süntar et al 2010;Wolfle et al 2014).…”
Section: Foxp3mentioning
confidence: 99%
“…bei Wundheilungsstörungen in großen Teilen Europas eine lange Tradition. In den vergangenen Jahren konnte die entzündungshemmende und wundheilungsfördernde Wirkung von Johanniskrautauszügen auch in vitro und in vivo nachgewiesen werden [19,22,23]. Einige der für die vorliegende Studie befragten Pferdehalter wendeten Johanniskrautöl extern zur Behandlung von Verspannungen der Rückenmuskulatur und bei akuten Tendinitiden an.…”
Section: Ergebnisse Und Diskussionunclassified
“…Topical application of St John's wort (Hypericum perforatum L.) extract [1], marigold (Calendula officinalis L.) extract [2,3], wheat (Triticum vulgare L.) germ oil [4] and rose (Rosa damascena L.) oil [5] for various topical treatment approaches due to anti-inflammatory, antimicrobial and healing effects indicated in scientific literatures. In this direction, combination of above mentioned herbal ingredients together in a formulation, which is cosmetically acceptable, stable, easily prepared and applicable, will be useful for the skin disorders.…”
Section: Introductionmentioning
confidence: 99%